Pendidikan Pesantren, Pluralisme, dan Radikalisme Agama: Studi Multi Kasus Pesantren di Kabupaten Jember: Islamic Boarding School Education, Pluralism, and Religious Radicalism: A Multi-Case Study of Islamic Boarding Schools in Jember Regency - Hidayati, Titiek Rohanah (LP2M UIN KH.Achmad Siddiq Jember, 2012)
Different perspectives among the Islamic boarding schools studied revealed similarities in the ideological context they develop, including an Islamic understanding based on Ahlus Sunnah Wal Jamaah. The differing responses occur not only within the boarding schools but also in society, which sometimes provides direct feedback and teaches students knowledge rooted in Ahlus Sunnah Wal Jamaah. Some boarding schools are less reactive to issues of religious radicalism. Nurul Islam and As Sumiyah Islamic Boarding Schools share nearly identical views on the problem of religious radicalism in Jember, both completely intolerant of radicalism. Meanwhile, Riyadhus Sholihin and Al Fatah Islamic Boarding Schools attempt to implement dialogic models. Perbedaan pandangan di antara pesantren yang diteliti ternyata memiliki kesamaan dalam konteks ideologi yang dikembangkan, termasuk pemahaman Islam yang berlandaskan Ahlus Sunnah Wal Jamaah. Perbedaan respons tidak hanya terjadi di dalam pesantren, tetapi juga di masyarakat yang terkadang memberikan tanggapan langsung dan mengajarkan santrinya pengetahuan berdasarkan Ahlus Sunnah Wal Jamaah. Ada pula pesantren yang tidak terlalu reaktif terhadap isu radikalisme agama. Pesantren Nurul Islam dan As Sumiyah memiliki pandangan yang hampir sama dalam menyikapi masalah radikalisme agama di Jember. Keduanya sama sekali tidak mentolerir radikalisme. Sementara itu, Pesantren Riyadhus Sholihin dan Al Fatah mencoba menerapkan model dialog.